2020
DOI: 10.1145/3416308
|View full text |Cite
|
Sign up to set email alerts
|

Gaming for Meaningful Interactions in Teleworking Lessons Learned during the COVID-19 Pandemic from Integrating Gaming in Virtual Meetings

Abstract: The recent need for social-distancing caused by COVID-19 resulted in working remotely, which can cause loneliness and disconnect from the organization. The pandemic stimulated people to look for novel ways to interact and, at the same time, socialize with each other. The change to home office increased the number of people using digital video calls; however, these impose restrictions on social bonding. In this commentary, we argue that the social bonding capacity of video calls can be increased by using games.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 9 publications
(9 reference statements)
0
4
0
Order By: Relevance
“…This is also supported by Protection Motivation Theory (PMT) [35]. The increased social bonding during the COVID-19 place confinement [36][37][38] may prompt people to take action and get vaccinated if they perceive the virus to be a serious threat [39]. On the other hand, it is also possible that social bonding engagement might promote information sharing about perceived threats of the COVID-19 vaccines leading to vaccine hesitancy.…”
mentioning
confidence: 99%
“…This is also supported by Protection Motivation Theory (PMT) [35]. The increased social bonding during the COVID-19 place confinement [36][37][38] may prompt people to take action and get vaccinated if they perceive the virus to be a serious threat [39]. On the other hand, it is also possible that social bonding engagement might promote information sharing about perceived threats of the COVID-19 vaccines leading to vaccine hesitancy.…”
mentioning
confidence: 99%
“…Similar to surgery and medica tasks, industrial and physical tasks [3], [18], [19], [20] also typically involve AS and SC roles. Lastly, in social and gaming [21], [22], [23] tasks, all three intermediate roles addressed where there exist various solutions to carry out such tasks.…”
Section: Tasks For Different Intermediary Rolesmentioning
confidence: 99%
“…Despite a large body of research on remote work and communication technologies that attempt to support remote collaboration [33,37,49] and recent discussions around the impact of the pandemic on remote work [63], few studies have considered how remote work affects interaction patterns among workers and how workers' perceptions of their remote colleagues might vary depending on the social connectivity with one another. Recent studies revealed that the pandemic has harmed remote workers' productivity [21,44,55], well-being [55], the social connection among remote collaborators [20,32], and the communication process when working from home [26,56]. However, what is not yet clear is the impact of specific tie strength, which is an important [63] but often overlooked social factor, on remote workers' perceptions when all communication becomes mediated by technology during work from home (WFH).…”
Section: Introductionmentioning
confidence: 99%